Starting a National Conversation. (January 2015) - Lundmark, Vicki
<x xml:space="preserve">Abstract</x> In this month's column, the director of research for the American Nurses Credentialing Center discusses outcomes of the Institute of Medicine Workshop on Credentialing Research in Nursing.